Presuposisi Faktif dalam Tindak Tutur Ilokusi Membual di Desa Karang Jati, Kecamatan Pandaan, Kabupaten Pasuruan - Muhammad Fikri Nur Ramadhan; Danang Wijoyanto (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Presuppositions are one of the topics of pragmatic semantics. This presupposition is the speaker's assumption of the speaker. This presupposition is present in every speech act and is often encountered. As in the illocutionary speech act of boasting (TTIM), people usually use TTIM to brag about themselves and to exalt themselves. There are several types of assumptions or presuppositions, one of which is factive presupposition. This presupposition exists every time a speaker performs the illocutionary speech act of boasting. This factive presupposition is always present in everyday activities. The theory used is the presupposition type theory from Yule (2006). Meanwhile, for speech act theory, Ibrahim (1993) is used. Based on this research, a total of 6 types of factive presuppositions were found in the illocutionary speech act of boasting in Karang Jati Village, Pandaan District, Pasuruan Regency by dividing the types of factive presuppositions based on general illocutionary speech acts based on their purpose which was divided into 6 types. The types of general illocutionary speech acts based on their purpose are crossed with 3 types of miter speech responses.